Research on curriculum and instruction in digital intelligence empowered engineering education based on first principles - Xiaotao, Zheng; Linwei, Ma (Frontiers in Education, 2025)
Facing the challenges of cultivating complex and innovative engineering talents, this study explores the innovation of engineering education and teaching empowered by digital intelligence based on first principles. By deconstructing the core connotations of education and learning, it emphasizes that university education needs to stimulate students‘ proactive exploration abilities and metacognitive development while respecting individual differences and implementing tailored teaching. The study finds that the first principles of education (holistic education) and learning (active construction) jointly drive the realization of educational goals through a six-dimensional dialectical unity. To further address the current problems in engineering education, such as insufficient student motivation and insufficient scientific nature of teaching evaluation, the study constructs a four-dimensional implementation path integrating digital intelligence. This includes using big data analysis to understand student learning situations and intelligent agents to achieve smart companion learning, using AI algorithms to recommend resources for personalized learning path planning, using project-led teaching to enhance engineering innovation training, and improving the digital capability development system for teachers to promote the knowledge graph integration of teaching resources. The study shows that digital intelligence technology, by reconstructing the resource supply model and optimizing process evaluation standards, has become a key way to implement first principles teaching strategies. It not only promotes teaching from “experience-driven” to “data-driven” but also supports lifelong capability development through the full life cycle learning portrait. Based on theoretical research, the study also demonstrates the promoting effect of digital intelligence empowerment on students' ability development through the innovative teaching practice of mechanical engineering students in the past 3 years.